Total synthesis of (-)-(6R,11R,14S)-colletallol via proline catalyzed alpha-aminoxylation and Yamaguchi macrolactonization - Kauloorkar, Shruti Vandana; Kumar, Pradeep (RSC Advances, 2016)
A simple and efficient synthesis of the 14-membered macrolide (-)-(6R,11R,14S)-colletallol was achieved in a highly diastereoselective manner with high overall yield. The stereogenic centre was generated using a proline catalyzed alpha-aminoxylation reaction and the ring was constructed using Yamaguchi protocol.